2016
DOI: 10.1186/s13071-016-1539-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Theileria equi and Babesia caballi infections in equine populations in Egypt by molecular, serological and hematological approaches

Abstract: BackgroundEquine piroplasmosis (EP) caused by Theileria equi, Babesia caballi, or both, contributes to significant economic loss in the equine industry and remains uncontrolled in Egypt. This study focuses on surveying T. equi and B. caballi infections and hematological disorders in equine populations in Egypt.MethodsTheileria equi and B. caballi infections were assessed in blood from 88 horses and 51 donkeys in Egypt using light microscopy, indirect immunofluorescent antibody test (IFAT), nested PCR (nPCR), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
66
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 32 publications
11
66
3
1
Order By: Relevance
“…These authors showed that there was heterogeneity in the 18S rRNA gene both for T. equi and B. caballi in Spain and South Africa. In support of our study and focusing on the RAP-1 gene of B. caballi , Bhoora et al [15], Rapoport et al [79] and Mahmoud et al [62] indicated failure to detect the B. caballi parasite. In accordance with Rapoport et al [79], there could be doubts as to the ability of the cELISA to serve as a sole regulatory test for the international horse trade.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These authors showed that there was heterogeneity in the 18S rRNA gene both for T. equi and B. caballi in Spain and South Africa. In support of our study and focusing on the RAP-1 gene of B. caballi , Bhoora et al [15], Rapoport et al [79] and Mahmoud et al [62] indicated failure to detect the B. caballi parasite. In accordance with Rapoport et al [79], there could be doubts as to the ability of the cELISA to serve as a sole regulatory test for the international horse trade.…”
Section: Discussionsupporting
confidence: 83%
“…equi vs. B . caballi)Predominant parasiteReferencesCFTAmericaBrazil58228.5 and 54.6 B. caballi  >  T. equi Kerber et al 2009 [53]EuropeFrance44358 and 12.9 T. equi  >  B. caballi Guidi et al 2015 [38]ELISAAfricaEgypt8814.8 and 0 T. equi  >  B. caballi Mahmoud et al 2016 [62]Sudan15863.5 and 4.4 T. equi  >  B. caballi Salim et al 2008 [85]AmericaBrazil4781 and 90 B. caballi  >  T. equi Xuan et al 2001 [104]Brazil58226.6 and 69.6 B. caballi  >  T. equi Kerber et al 2009 [53]Brazil19878.3 and 69.2 T. equi  >  B. caballi Vieira et al 2013 [100]…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, sensitive and specific tests for Equine Piroplasmosis diagnosis are required to prevent introduction of causative agents into countries that are regarded free of the infection or disease (Mahmoud et al 2016).The results presented here indicate that PCR is a sensitive assay and proves that the causative agents of Equine Piroplasmosis are circulating in the studied area. Studies performed in Brazil using PCR or IFAT have also detected both agents in horses, as the one reported in Minas Gerais (Heim et al 2007), Rio Grande do Sul (Torres et al 2012), Rio de Janeiro (Peckle et al 2013) and São Paulo (Dória et al 2016).…”
Section: Discussionmentioning
confidence: 70%
“…The diagnoses of Equine Piroplasmosis can be done by direct and indirect methods; however, molecular assays appears as useful tools to identify the infection (Figueroa et al 1993, Bashiruddin et al 1999, Nicolaiewsky et al 2001, Peckle et al 2013, Malekifard et al 2014, Dória et al 2016, Mahmoud et al 2016. Therefore, sensitive and specific tests for Equine Piroplasmosis diagnosis are required to prevent introduction of causative agents into countries that are regarded free of the infection or disease (Mahmoud et al 2016).The results presented here indicate that PCR is a sensitive assay and proves that the causative agents of Equine Piroplasmosis are circulating in the studied area.…”
Section: Discussionmentioning
confidence: 99%
“…A significant degree of agreement between the tests was found in a comparative study by Vieira et al (2015). Other serological studies using these two tests also showed almost perfect agreement between them (GOLYNSKI et al, 2008;SALVAGNI et al, 2010;FARKAS et al, 2013;MAHMOUD et al, 2016). However, IFA tested an increased number of 19 horses with anti-T. equi antibodies titer in comparison with ELISA which tested only 10/19 horses with anti-T. equi antibodies titer (PIKALO et al, 2016).…”
Section: Discussionmentioning
confidence: 78%